Crime and Insecurity in Rivers State: The Need for Utilization of OSPAC Security as Alternative Security Measure in Rivers State - Emeodu Elijah Nwabueze; Etire John George; Dickson Johnwill Kalio; Oscar Inowei Alabo (International Journal on Integrated Education, 2022)
This study examined crime and insecurity in Rivers State: The need for utilization of OSPAC security as alternative security measure in Rivers State. The study adopted three (3) research questions and objectives and they constituted the study guide. Thus, the self determination theory of Edward Deci and Richard Ryan (1985) was adopted as the theoretical framework for the study. The survey research design was used, with sample size of 396 using Taro Yameni. Data instrument was questionnaire. Hence, the data was analyzed using simple percentages, mean and standard deviation. The findings of the study shows that the reasons or the need for alternative security measures using OSPAC security to support the failed conventional security is to combat crime and insecurity in Rivers State which has hypnotize growth and development. The study recommended that since crime and insecurity spellbind growth and development, there is need for government, communities, NGOs and stakeholders who are concerned about human lives and security to provide alternative security and sustain such security outfit, as this can help improve security conditions in Rivers State.